Nasal Complications Related With Cpap Treatment - Gökdoğan, Ozan; İleri, Fikret (ENT Updates, 2018)
AIM: In preterm infants who have a tendency for hypoxia, continuous positive airway pressure (CPAP) support is one of the standard treatments being used today. Although newborns are prone to complications, too many complications have not been reported in literature due to CPAP in newborn period. In this study, complications in preterm infants have been reported who had nasal CPAP treatment which were considered to be related to this. METHOD: Within the scope of the study, 82 babies who were hospitalized in the newborn intensive care unit and had nasal CPAP between September 2014 and September 2017 have been evaluated. During this time period, the newborns that had nasal CPAP treatment have been evaluated in terms of nasal complications in certain intervals. RESULTS: During this period, complications which are considered to be related to Nasal CPAP have been observed in 6 babies. In 4 newborns, nasal columellar hyperemia related to the use of masks and in 1 newborn, columella necrosis has been seen. In two of the patients, intranasal synechia has been observed. While intranasal synechias were unilateral in 1 patient, it was observed as bilateral multiple nasal synechia in another patient. CONCLUSION: Continuous positive airway pressure treatment is a lifesaving method when required. However, it may cause certain complications due to pressure and pressured air in the newborn period which is open to all kinds of trauma. It is important to know about these complications and identifying and preventing them in the earliest time possible since the treatment is long and difficult.